background image

16.7. MORE ON PROPERTIES OF FUNCOIDS

267

16.7. More on properties of funcoids

Proposition

1403

.

Γ(

A, B

) is the center of lattice

FCD

(

A, B

).

Proof.

Theorem

610

.

Proposition

1404

.

up

Γ(

A,B

)

(

A ×

FCD

B

) is defined by the filter base

n

A

×

B

A

up

A

,B

up

B

o

on the lattice Γ(

A, B

).

Proof.

It follows from the fact that

A ×

FCD

B

=

d

FCD

n

A

×

B

A

up

A

,B

up

B

o

.

Proposition

1405

.

up

Γ(

A,B

)

(

A ×

FCD

B

) =

F

(Γ(

A, B

))

up(

A ×

RLD

B

).

Proof.

It follows from the fact that

A ×

FCD

B

=

d

FCD

n

A

×

B

A

up

A

,B

up

B

o

.

Proposition

1406

.

For every

f

F

(Γ(

A, B

)):

1

.

f

f

is defined by the filter base

n

F

F

F

up

f

o

(if

A

=

B

);

2

.

f

1

f

is defined by the filter base

n

F

1

F

F

up

f

o

;

3

.

f

f

1

is defined by the filter base

n

F

F

1

F

up

f

o

.

Proof.

I will prove only

1

and

2

because

3

is analogous to

2

.

1

It’s enough to show that

F, G

up

f

H

up

f

:

H

H

v

G

F

. To

prove it take

H

=

F

u

G

.

2

It’s enough to show that

F, G

up

f

H

up

f

:

H

1

H

v

G

1

F

.

To prove it take

H

=

F

u

G

. Then

H

1

H

= (

F

u

G

)

1

(

F

u

G

)

v

G

1

F

.

Theorem

1407

.

For every sets

A

,

B

,

C

if

g, h

F

Γ(

A, B

) then

1

.

f

(

g

t

h

) =

f

g

t

f

h

;

2

. (

g

t

h

)

f

=

g

f

t

h

f

.

Proof.

It follows from the order isomorphism above, which preserves compo-

sition.

Theorem

1408

.

f

g

=

f

u

FCD

g

if

f, g

Γ(

A, B

).

Proof.

Let

f

=

X

0

×

Y

0

. . .

X

n

×

Y

n

and

g

=

X

0

0

×

Y

0

0

. . .

X

0

m

×

Y

0

m

.

Then

f

g

=

[

i

=0

,...,n,j

=0

,...,m

((

X

i

×

Y

i

)

(

X

0

j

×

Y

0

j

)) =

[

i

=0

,...,n,j

=0

,...,m

((

X

i

X

0

j

)

×

(

Y

i

Y

0

j

))

.

But

f

=

X

0

×

Y

0

t

FCD

. . .

t

FCD

X

n

×

Y

n

and

g

=

X

0

0

×

Y

0

0

t

FCD

. . .

t

FCD

X

0

m

×

Y

0

m

;

f

u

FCD

g

=

l

i

=0

,...,n,j

=0

,...,m

((

X

i

×

Y

i

)

u

FCD

(

X

0

j

×

Y

0

j

)) =

l

i

=0

,...,n,j

=0

,...,m

((

X

i

u

X

0

j

)

×

FCD

(

Y

i

u

Y

0

j

))

.

Corollary

1409

.

If

X

and

Y

are finite binary relations, then

1

.

X

u

FCD

Y

=

X

u

Y

;

2

. (

> \

X

)

u

FCD

(

> \

Y

) = (

> \

X

)

u

(

> \

Y

);

3

.

X

u

FCD

(

> \

Y

) =

X

u

(

> \

Y

).